The Phenomenon Of Foreign Fighters And International Obligations To Confront It - محمد مصطفى كريز (Latakia University Journal - Economic and Legal Sciences Series, 2022)
Foreign fighters leave their home country or country of habitual residence to join an armed group whose doctrine or ideology they believe in. This phenomenon, which witnessed unprecedented activity in the past decade, has become one of the most important concerns of the international community because of the threat it poses to international peace and security, especially since the largest number of these fighters joined armed groups that have been classified as terrorists, such as the Islamic State in Iraq and the Levant. In order to confront this phenomenon, it is necessary for each of the states to which the foreign fighters belong by nationality or the state in which they live, the states they cross into their territory, and the state they intend to participate in the fighting on its territory to fulfill the obligations imposed on them under international law.